Faktor-faktor yang Memengaruhi Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan Pedesaan dan Perkotaan di Kabupaten Sumbawa Besar - Nengah Lili Setiawati; Endang Kartini; Rusli Amrul; Ni Nyoman Yuliati (Kompeten: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This Study aims to determine the factors that influence taxpayer compliance in paying land and building taxes in rural and urban areas n Sumbawa Besar Regency. The research method used in this studyis a quantitative method with an associative approach. The variables of this study consist of 5 (five) independent variables, namely tax knowledge (X1), taxpayer awareness (X2). Income level (X3), quality of tax services (X4) and tax sanctions (X5) and dependent variable, namely taxpayer compliance (Y). The population in this study were 236,606 taxpayers registered at the Sumbawa Besar Bapenda. The sample was taken using the slovin formula so that the sample obtained was 100 respondents. The sampling technique used in this study is Incidental Sampling. Data was obtained by distributing questionnaires to tax payers int he Sumbawa Besar district. The results showed that knowledge of taxation had a positive and significant effect on taxpayer compliance, while tax payer awareness,incomelevels, quality of tax services and taxsanctions had no effect on tax payer compliance in paying land and building taxes.